2019
DOI: 10.1155/2019/7124072
|View full text |Cite
|
Sign up to set email alerts
|

ST-Elevation Myocardial Infarction (STEMI) in a Patient with Moyamoya Disease

Abstract: Moyamoya disease is a rare condition that is primarily reported in Asian populations, characterized by stenoocclusive intracranial angiopathy with small, fragile, and multiple collateral vessel formation. Extracranial complications, mainly abnormalities within the renal vasculature, have been described; however, there are very few case reports of cardiovascular complications in patients with Moyamoya disease. We report a 26-year-old Caucasian female with known Moyamoya disease who presented with both typical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Interestingly, a recent case report by James Livesay and Jeffrey Johnson indicated a direct incidence of STEMI in an MMD patient. Perhaps, to the best of our knowledge, this is one of the first-in-class direct case reports of CAD in a Caucasian female with reported MMD, presenting with cerebral vasculature complications ( 79 ). They emphasized a critical notion that extracranial vascular complications in MMD patients are rare but can significantly impact a patient’s overall morbidity and mortality.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Interestingly, a recent case report by James Livesay and Jeffrey Johnson indicated a direct incidence of STEMI in an MMD patient. Perhaps, to the best of our knowledge, this is one of the first-in-class direct case reports of CAD in a Caucasian female with reported MMD, presenting with cerebral vasculature complications ( 79 ). They emphasized a critical notion that extracranial vascular complications in MMD patients are rare but can significantly impact a patient’s overall morbidity and mortality.…”
Section: Discussionmentioning
confidence: 88%
“…MMD could likely lead to occlusion of coronary arteries through certain systemic etiologic factors in the blood. Many other studies also supported a correlation between MMD and CAD (67,79). Now, concerning the RA cases, a recent report showed that a patient with a history of RA for 15 years also suffered from cerebral rheumatoid vasculitis (81).…”
Section: Redisx Supports Advancing the Screening Of Precise Druggable...mentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, Xing Peng et al discovered that MDD patients with downregulated GZMB were also enriched with the downregulated genes of CAD (Peng et al, 2019). Many other studies also supported a correlation between MDD and CAD (Livesay & Johnson, 2019;Nam et al, 2015). Concerning the RA cases, a recent report showed that a patient with a history of RA for 15 years also suffered from cerebral rheumatoid vasculitis (El-Sudany et al, 2021).…”
Section: Redisx Supports Advancing the Screening Of Precise Druggable...mentioning
confidence: 97%